A COMPARATIVE STUDY OF PHYSICAL AND DIGITAL COMMUNICATION METHODS IN THE MODERN WORLD - Rani, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
There has been a remarkable change in communication over the last few decades. Because of digital technologies, face-to-face, letter and newspaper interactions are now commonly used together with emails, instant messaging, video calls and social media platforms. This paper investigates the benefits; shortcomings and what people prefer in using different communication methods today. The study looks into how different technologies are used, how well they work, how trusted they are and what effect they have on human relationships by using both descriptive statistics and hypothesis testing. There is clearly a rise in digital communication, while still some cases rely on more traditional ways to communicate.